Program Sosialisasi Pengolahan Kotoran Sapi Menjadi Biogas Di Sanjaya Farm, Lampung - Lathifa Putri Afisna; Devia Gahana Cindi Alfian; Ilham Dwi Arirohman; Muhammad Syaukani; Achmad Gus Fahmi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Unmitigated cow dung waste possesses the capacity to induce pollution and environmental degradation, hence potentially compromising air quality and the well-being of the neighboring population. The objective of this Community Service initiative is to enhance community understanding and promote the adoption of biogas technology as a sustainable energy alternative within livestock communities in the Sukabumi district of Lampung Province. The approach of socialization and direct instruction employed in this study involves educating farmers and local populations on the effective treatment of cow dung waste, thereby mitigating environmental degradation and harnessing waste as a valuable energy resource. Pretest and posttest questionnaires were administered to assess participants' comprehension levels and evaluate the outcomes of the socialization process. According to the responses obtained from the questionnaires completed by the participants, a significant majority (90%) acknowledged the existence of environmental consequences associated with untreated cow dung. Furthermore, an overwhelming majority (99%) expressed agreement with the idea of converting cow dung into biogas. Additionally, a substantial proportion (90%) of the participants reported an enhanced comprehension of the process involved in converting cow dung into biogas. This phenomenon demonstrates that the community's view necessitates the integration of technology in order to address their issues. Hence, the utilization of suitable technology is imperative for the community, particularly cattle farmers, to effectively manage the disposal of cow dung waste, which significantly affects the environment. The utilization of biogas technology has the potential to mitigate this impact and offer alternative energy alternatives that are more ecologically sustainable for the local community.